The impact of stock market development on foreign direct investment in Nigeria: An application of autoregressive distributed lag model - Murtala, Bala Umar; Suraya, Ismail; Zunaidah, Sulong (2015)
Stock market development is essential for economic growth and prosperity in developing economies like Nigeria. Foreign Direct net flow plays a vital role in promoting economic growth through boosting the stock market development of both emerging economies, as well as developed nations. The largest numbers of the emerging economies are integrated and pursuing their international operations due to foreign direct investment. This paper investigates the impact of the stock market variables on foreign direct investment using autoregressive distributed lag (ARDL) in the presence of structural breaks (dummies) in Nigeria. The study utilized annual time series data from 1970 to 2013. The data were generated from World Bank and Central Bank of Nigeria (CBN). The result suggests that the foreign direct investment (FDI) has a significant positive long-run impact on the value of the total stock transaction, but has a negative and significant effect on the rate of stock returns. However, the relationship between FDI and market capitalization ratio is not statistically significant. Based on these findings the stock market value of the total transaction promotes FDI and thus boosts economic growth and development in Nigeria.